Potret Keberadaan Kesenian Wayang Kulit di Bekasi: Wayang Kulit Akulturasi (Periode Tahun 1970-2015) - Dalila Kusuma Wardani; Didin Saripudin (Universitas Pendidikan Indonesia dan APPS (Asosiasi Pendidik dan Peneliti Sejarah), 2021)
This article aims to describe the development of wayang kulit in Bekasi in 1970-2015. Broadly speaking, the main problem studied in this article is about